2023
DOI: 10.1037/edu0000796
|View full text |Cite
|
Sign up to set email alerts
|

Writing motives and writing achievement of elementary school students from diverse language backgrounds.

Abstract: This study examined the intrinsic, extrinsic, and self-regulatory motives for writing and writing achievement of three groups of third- to fifth-grade students in an urban school district: (a) 189 emergent bilingual students receiving services for English language development (ELD); (b) 374 reclassified bilingual students who had exited ELD programs; and (c) 563 native English-speaking students. Intrinsic and self-regulatory writing motives were significantly higher for emergent bilingual students and reclassi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
1
0
1
Order By: Relevance
“…Maksud dari tulisan deskripsi adalah untuk menciptakan gambaran yang kuat bagi para pembaca, memungkinkan mereka untuk membayangkan atau merasakan objek tersebut secara visual, sesuai dengan penelitian oleh Sutarni dan Sukardi (2008). Karena itu, penting sekali bagi seorang siswa untuk dapat menyusun gagasan mereka dengan rinci, metode yang teratur, dan dengan jelas agar tulisan mereka mudah dimengerti oleh pembaca (Al-Daghi, 2022;Alfulaila, 2019;Babayigit, 2019;Camping, 2023;Chang, 2019;Chávez, 2018;Cheung, 2019;Costa, 2018;Escott, 2022;Göçen, 2019;Grenner, 2021;Istiq'faroh, 2020;Kara, 2022;Laila, 2021;Pohlmann-Rother, 2020;Zapata, 2022;Zugelder, 2023). Namun, masih ditemukan banyak siswa yang menghadapi kesulitan dalam menulis teks deskripsi yang memenuhi standar bahasa yang benar (Curcic, 2019;Habibi, 2020;Launder, 2022;Nugraha, 2019;Oliveira, 2019;Ortega, 2021;Rohloff, 2023;Spence, 2018;Walls, 2023).…”
Section: Pendahuluanunclassified
“…Maksud dari tulisan deskripsi adalah untuk menciptakan gambaran yang kuat bagi para pembaca, memungkinkan mereka untuk membayangkan atau merasakan objek tersebut secara visual, sesuai dengan penelitian oleh Sutarni dan Sukardi (2008). Karena itu, penting sekali bagi seorang siswa untuk dapat menyusun gagasan mereka dengan rinci, metode yang teratur, dan dengan jelas agar tulisan mereka mudah dimengerti oleh pembaca (Al-Daghi, 2022;Alfulaila, 2019;Babayigit, 2019;Camping, 2023;Chang, 2019;Chávez, 2018;Cheung, 2019;Costa, 2018;Escott, 2022;Göçen, 2019;Grenner, 2021;Istiq'faroh, 2020;Kara, 2022;Laila, 2021;Pohlmann-Rother, 2020;Zapata, 2022;Zugelder, 2023). Namun, masih ditemukan banyak siswa yang menghadapi kesulitan dalam menulis teks deskripsi yang memenuhi standar bahasa yang benar (Curcic, 2019;Habibi, 2020;Launder, 2022;Nugraha, 2019;Oliveira, 2019;Ortega, 2021;Rohloff, 2023;Spence, 2018;Walls, 2023).…”
Section: Pendahuluanunclassified
“…Likewise, in their review of research on writing attitudes, Ekholm et al (2018) reported that girls have more positive attitudes than boys ( Ekholm et al, 2018 ). While there is no current systematic review of relations between writing motivational beliefs and students’ language status, individual studies such as those conducted by Camping et al (2020 , 2023) demonstrated that language status predicts students’ beliefs about writing.…”
Section: Introductionmentioning
confidence: 99%